konnect2prot 2.0: Integrating advanced analytical tools for deeper understanding of protein properties in a functional protein-protein interaction network - Shivam Kumar; Abhinav Agarwal; Dipanka Tanu Sarmah; Samrat Chatterjee (Computational and Structural Biotechnology Journal)
Proteins work in coordination to catalyze and regulate all biological activities and drive cellular functions. The collective behavior of proteins is studied through protein-protein interaction (PPI) networks, which provide a system-level understanding of their regulatory behavior. konnect2prot (k2p) is a web application that generates a context-specific directional PPI network from a list of proteins as input. It identifies influential spreaders in the generated network and detects their biological and topological importance. Here, we report the features added to k2p since its first release. Building on the foundation of its predecessor, k2p 2.0 now integrates differential gene expression analysis, thereby bridging the gap between gene-level regulation and protein-level activity, providing a holistic view of how transcriptional changes fuel cellular behavior. konnect2prot 2.0 is freely accessible at: https://konnect2prot_v2.thsti.in.